The Effectiveness of School-Based Lesson Study in Improving Teacher’s Competence in Learning Indonesian Language in SD IT Tumaninah Yasin Metro Academic Year 2020/2021 - Iramaya, Nila; Supriyono, Supriyono; Permanasari, Dian; Windriani, Dian (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2021)
The problems raised in this study is related to the effectiveness of school-based lesson study in an effort to improve teacher competency. This study is conducted with the aim of improving the competency of Indonesian language teachers at SD IT Tumaninah Yasin Metro for the 2020/2021 academic year. The results shows that the implementation of the teacher's ability done in cycle I and cycle II. The meeting in the first cycle of the implementation of the teacher's ability in planning learning is 78.3% and the implementation of the teacher's ability in the implementation of learning is 77.9%. The implementation of the learning evaluation is 79.1%, this value is lower than the total value in the second cycle, namely the implementation of the teacher's ability to plan learning of 84, 2% and the implementation of the teacher's ability in the implementation of learning is 86.3%. However, the implementation of the learning evaluation is 87.5%. The conclusion obtained from this study is that the implementation of lesson study at SD IT Tumaninah Yasin Metro based on the research findings in cycle I and cycle II as a whole can improve the pedagogic competence of Indonesian language teachers at SD IT Tumaninah Yasin Metro. The implementation of lesson study at SD IT Tumaninah Yasin Metro on the performance of teachers in doing the lesson study stage in each cycle has increased. It is hoped that the support from various parties can cintinue and sustain the implementation of school-based lesson study.